Social and psychological characteristics of economic socialization in puberty - Nekipelova, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article describes the main approaches to understanding the process of economic socialization during puberty, and the social and psychological determinants of entry into the world economy by teenager.
Keywords: economic socialization; teenager; world of economy; social and psychological substance